Binary Opposition between Characters against Myths in the Novel Begu Ganjang by Ferdiriva Hamzah - Telaumbanua, Ester Anugrah; Sayuti, Sumito A; Sari, Selvia Aniffah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyse the narrative construction in a novel by Ferdiriva Hamzah that explores the myth of Begu Ganjang. The study investigates how traditional narratives passed down through generations become the subject of debate in the context of contemporary society. The focus of the analysis lies on the dynamics between the characters, where the main character who tends to represent the values of modernity and rationality confronts the supporting characters who still adhere to traditional beliefs. This research examines the contestation of binary oppositions that emerge from the tensions that occur as reflected in the interactions between characters in the novel. This research method applies a descriptive qualitative approach, using Levi-Strauss' structuralism analysis framework to analyse the mythological construction process. The Levi-Strauss structuralism paradigm is applied to obtain a comprehensive understanding of the phenomenon of the Begu Ganjang myth in the socio-cultural context of Batak society. This study aims to explore and analyse the contradictions that occur in the characters in the narrative of the Begu Ganjang myth. In Levi-Strauss' structuralist perspective, this opposition is conceptualised as binary opposition.